Quality of Acute Psychedelic Experience Predicts Therapeutic Efficacy of Psilocybin for Treatment-Resistant Depression - Roseman, Leor; Nutt, David J.; Carhart-Harris, Robin L. (Frontiers in Pharmacology, 2018)
Introduction: It is a basic principle of the ‘psychedelic’ treatment model that the quality of the acute experience mediates long-term improvements in mental health. In the present paper we sought to test this using data from a clinical trial assessing psilocybin for treatment-resistant depression (TRD). In line with previous reports, we hypothesized that the occurrence and magnitude of Oceanic Boundlessness (OBN) (sharing features with mystical-type experience) and Dread of Ego Dissolution (DED) (similar to anxiety) would predict long-term positive outcomes, whereas sensory perceptual effects would not. Material and Methods: Twenty patients with treatment resistant depression underwent treatment with psilocybin (two separate sessions: 10mg and 25mg psilocybin). The Altered States of Consciousness (ASC) questionnaire was used to assess the quality of experiences in the 25mg psilocybin session. From the ASC, the dimensions OBN and DED were used to measure the mystical-type and challenging experiences, respectively. The Self-Reported Quick Inventory of Depressive Symptoms (QIDS-SR) at 5 weeks served as the endpoint clinical outcome measure, as in later time points some of the subjects had gone on to receive new treatments, thus confounding inferences. In a repeated measure ANOVA, Time was the within-subject factor (independent variable), with QIDS-SR as the within-subject dependent variable in baseline, 1-day, 1-week, 5-weeks. OBN and DED were independent variables. OBN-by-time and DED-by-time interactions were the primary outcomes of interest. Results: For the interaction of OBN and DED with Time (QIDS-SR as dependent variable), the main effect and the effects at each time point compared to baseline were all significant (p = 0.002 and p = 0.003, respectively, for main effects), confirming our main hypothesis. Furthermore, Pearson’s correlation of OBN with QIDS-SR (5 weeks) was specific compared to perceptual dimensions of the ASC (p < 0.05). Discussion: This report further bolsters the view that the quality of the acute psychedelic experience is a key mediator of long-term changes in mental health. More specifically, future therapeutic work with psychedelics may consider investigating ways which enhance mystical-type experience and reduce anxiety, given the growing evidence that this serves the efficacy of the treatment model.